RIBA DALAM ALQURAN (Suatu Kajian Dengan Pendekatan Maudhu’iy) - M., Amiruddin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
Islamic Law in principle be dynamic, flexible and elastic to maintain a balance between the principles of Islamic rules' with the development of the world of thought, it is intended for the benefit of human life. Islamic law on property rights asserted material social functioning, therefore private property rights are not absolute, but related to social obligations. So the property owner does not fully treat her possessions, such as hoarding treasure, treasure spent in belebih exaggeration, using treasures to bribe, gamble, and trending thing not justified normative. Islamic law also regulates the development of property, Islamic law does not justify the development of the property by way of deprivation, oppression, or persecution, including the practice of usury, which is forbidden by Islamic law. Islamic scholars, Ulama agreed stating that the Koran clearly states usury laws is forbidden. Then differ in their views in response to the development of the monetary system or developments in economic transactions. When observed differences cleric and Islamic scholar in setting legal interest in the monetary system, it turns out that the difference arises because attitudes about their perspectives on the banking system. Ulema who justify seeing that the banking system is not as represented memperaktekkan riba riba in the Arab Jahiliyyah which is prohibited by the Koran. While scholars forbid, see the practice of usury in the banking system as riba is usury nasiah during Jahiliyyah